Identification of NF1 Frameshift Variants in Two Chinese Families With Neurofibromatosis Type 1 and Early-Onset Hypertension - Lu, Yi-Ting; Zhang, Di; Liu, Xin-Chang; Zhang, Qiong-Yu; Dong, Xue-Qi; Fan, Peng; Xiao, Yan; Zhou, Xian-Liang (Frontiers in Pediatrics, 2021)
Background: Neurofibromatosis type 1 (NF-1) is a common autosomal dominant disorder caused by mutations in the NF1 gene. It is characterized by multiple café-au-lait macules, cutaneous neurofibromas, optic glioma, Lisch nodules, and axillary and inguinal freckling. The aim of this study was to investigate NF1 mutations in two Chinese families with NF-1 who presented with early-onset hypertension, and to determine the prevalence of hypertension associated with NF-1 to better understand this complication. Methods: Whole-exome sequencing was performed for the probands with NF-1 from two unrelated families. Possible pathogenic mutation was predicted by bioinformatic tools. Sanger sequencing was used to confirm candidate variants in all available individuals for familial co-segregation analysis. We also performed a systematic literature review of studies that reported the prevalence of hypertension in patients with NF-1. Results: In family 1, a recurrent mutation c.6789_6792delTTAC in NF1 was identified in the proband but in no other family members, indicating that this is a de novo mutation. In family 2, a novel mutation c.6934_6936delGCAinsTGCT in NF1 was detected in the proband and two other family members, which co-segregated with the disease phenotype within the family. Both mutations were predicted to be pathogenic by bioinformatic analysis. We found hypertension was a relatively common complication of NF-1, with a prevalence range of 6.1–23.4%. Ambulatory blood pressure monitoring is a stable method for detecting initial alterations of the blood pressure pattern, particularly for pre-hypertension. Conclusions: We identified one recurrent (c.6789_6792delTTAC) and one novel frame-shift mutation (c.6934_6936delGCAinsTGCT) in two unrelated families with NF-1 using whole-exome sequencing. In consideration of phenotypic heterogeneity in NF-1, genetic testing is a robust tool which helps early and accurate diagnosis. Because hypertension is not a rare complication of NF-1, routine screening for hypertension in patients with NF-1, especially children and adolescents, is important to avoid serious cardiovascular events.